(untitled) (Revista Iberoamericana de Bioética, 2021)
Human rights are often understood as a kind of unlimited individual power that can be permanently appealed to, but a right is always limited. During a health emergency where there are finite and insufficient resources, the rights of different people enter into conflict. The debate on the disproportionate burden of reasonable adjustments in accessibility actions parallels the justification of a triage process when health resources are limited. In any case, it should be understood that a burden is disproportionate only to the extent that it damages a legally superior protected asset.